Kewenangan Mahkamah Konstitusi dalam Pemakzulan Presiden dan/atau Wakil Presiden di Indonesia - Bambang Sutiyoso (The Constitutional Court of the Republic of Indonesia, 2016)
The idea of impeachment (pemakzulan) towards the incumbent president of Indonesia surfaces recently. This could be the cause of two main grounds. First, regarding the ongoing investigation process of the Century Bank case. In the beginning, the presumption charges merely towards the monetary policy officials and the concerning president’s assistants, but during the further investigations, a number of political parties, in not so vigorously manner pointed the charges to the incumbent presidents because of the indication of responsibility toward the bailout process of Century Bank. Second, the idea of presidential impeachment got its nudge when the Constitutional Court also declaring that its components are ready in processing the impeachment petition, after it has surfaced the Constitutional Court Rule (Peraturan Mahkamah Konstitusi) No. 21/PMK/2009 on the Guidelines in Judicial Procedures in Hearing the Parliamentary Petition in Violation Charges Towards President of the Republic and/or Vice President of the Republic. Third, Presidential and / or Vice Presidential Impeachments has already been occurred in the history of Indonesian nation, namely towards past Indonesian Presidents such as Sukarno, Suharto and KH. Abdurrahman Wahid.This writing attempts to discuss issues regarding presidential impeachment in Indonesia, such as the power of the Constitutional Court in impeachment process, the legal grounds of impeachments, reasons for impeachments and the procedural mechanism of impeachment. Constitutionally, the procedures and mechanism of presidential and / or vice presidential impeachment has been regulated comprehensively in the Constitution of the Republic of Indonesia, specifically in Article 7 B, Article 24 (2), and Article 24 C of the 1945 Constitution after the Third Amendment. Based on these regulations, impeachment is not a simple process, but requires a long process and involving a number of high state institutions, namely People’s Representative Council (DPR), The Constitutional Court, and People Consultative Assembly (MPR). The involvement of the Constitutional Court in the impeachment process can be related toward historical experiences and as a logical consequence of the constitutional transformation of Indonesia. Beside that, the idea of presidential and / or vice presidential impeachment should not be based merely on political motivation, but should also have the reasonable legal grounds and rationale.